2005
DOI: 10.1001/jama.293.7.836
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis of the Living Human Fetus Using Cell-Free Messenger RNA in Amniotic Fluid

Abstract: ECAUSE OF THE INHERENT DIF-ficulties with research on human fetuses, the analysis of fetal gene expression has in large part been limited to the examination of tissue from human abortuses and the assessment of animal models for genes and developmental pathways that are conserved across species. Fetal monitoring in vivo is limited to noninvasive methods such as the measurement of uterine size or anatomic evaluation by fetal sonography. In addition, genetic analysis can be performed on amniotic fluid components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
3
71
0
Order By: Relevance
“…A similar mechanism may also explain why vesicles derived from apoptotic cells are also highly enriched in mRNA. 27,28,37,38 In support of the concept of MV (e.g., ES-MV) playing a role in horizontal exchange of molecules between cells, it has been demonstrated that eucaryotic cells possess highly sophisticated membrane trafficking pathways that define specific membrane domains and provide a means for moving vesicles between them. Recently, it was demonstrated, for example, that cells cultured in vitro may exchange MV in so-called tunneling nanotubules.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism may also explain why vesicles derived from apoptotic cells are also highly enriched in mRNA. 27,28,37,38 In support of the concept of MV (e.g., ES-MV) playing a role in horizontal exchange of molecules between cells, it has been demonstrated that eucaryotic cells possess highly sophisticated membrane trafficking pathways that define specific membrane domains and provide a means for moving vesicles between them. Recently, it was demonstrated, for example, that cells cultured in vitro may exchange MV in so-called tunneling nanotubules.…”
Section: Discussionmentioning
confidence: 99%
“…3). The RNA was extracted, amplified, labeled and hybridized to either the Affymetrix U133A expression microarray (Larrabee et al 2005) or the Affymetrix GeneChip Human Genome U133 Plus 2.0 expression microarray (Slonim et al 2009;Koide et al 2011;Hui et al 2012aHui et al ,b, 2013aEdlow et al 2014;Massingham et al 2014). Despite the availability of more sophisticated expression microarrays, the U133 Plus 2.0 was chosen because of the need for compatibility with an essential downstream in silico tool, the Connectivity Map (Lamb et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Cell-free fetal RNA in amniotic fluid supernatant provides an opportunity to study fetal gene expression in real-time. questions about the effects of sex, GA, and disease on the transcripts present in AFS (Larrabee et al 2005). AF was obtained from four pregnancies in which each woman underwent therapeutic amnioreduction for polyhydramnios caused by twin -twin transfusion syndrome (TTTS) or fetal hydrops.…”
Section: Studies In the Developing Fetusmentioning
confidence: 99%
See 2 more Smart Citations